2021
DOI: 10.1002/adma.202102332
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Multifunctional Photonic‐Electronic Smart Skin for Ultrasensitive Health Monitoring, for Visual and Self‐Powered Sensing

Abstract: Smart skin is highly desired to be ultrasensitive and self‐powered as the medium of artificial intelligence. Here, an ultrasensitive self‐powered mechanoluminescence smart skin (SPMSS) inspired by the luminescence mechanism of cephalopod skin and the ultrasensitive response of spider‐slit‐organ is developed. Benefitting from the unique strain‐dependent microcrack structure design based on Ti3C2Tx (MXene)/carbon nanotube synergistic interaction, SPMSS possesses excellent strain sensing performances including ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
78
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 127 publications
(81 citation statements)
references
References 67 publications
0
78
0
Order By: Relevance
“…For example, in recent decades, the artificially intelligent robots predicted in sci‐fi movies have attracted increasing attention, and considerable effort has been devoted to studying the enhancement of perception and object manipulation capabilities of intelligent robots. [ 1–9 ] To mimic, or even beyond, the functions of a human hand, a robotic hand needs to be able to handle a complex surrounding pressure environment in practical applications. It has been demonstrated that the excellent pressure perception ability of the human hands is derived from a particularly interesting feature of the synergistic strategy of touch receptors and baroreceptors in human skin.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in recent decades, the artificially intelligent robots predicted in sci‐fi movies have attracted increasing attention, and considerable effort has been devoted to studying the enhancement of perception and object manipulation capabilities of intelligent robots. [ 1–9 ] To mimic, or even beyond, the functions of a human hand, a robotic hand needs to be able to handle a complex surrounding pressure environment in practical applications. It has been demonstrated that the excellent pressure perception ability of the human hands is derived from a particularly interesting feature of the synergistic strategy of touch receptors and baroreceptors in human skin.…”
Section: Introductionmentioning
confidence: 99%
“…Multifunctional flexible sensors, which can effectively solve the problem of the limited application range of single-performance sensors, have been widely studied in recent years [84]. Rao et al [85] proposed a sensor which can simultaneously detect pressure and temperature, composed of a thermosensitive electrode combining rGO and BiTO; the sensor is suitable for tactile e-skin (Figure 4a).…”
Section: Multifunctionmentioning
confidence: 99%
“…[29][30][31][32] These properties render MXene, a promising candidate for making a multi-responsive actuator with sensing function. [33][34][35][36][37] The actuation of our device is owing to the distinct volume variations between MXene coated-paper and PE under multifarious environmental stimuli, such as NIR light, temperature, and humidity. The sensing property is based on the piezoresistivity, thermoresistivity, and hygresistivity of the MXene coated-paper.…”
Section: Introductionmentioning
confidence: 99%